Clinical researchA survey on the distribution of healthy people with different anti-tumour ability - Gao, Yanhong; Xu, Xiaolan; Dong, Zhennan; Jiang, Chaoguang; Gao, Jin; Hu, Jinchuan; Gui, Junhao; Wang, Haibao; Tian, Yaping (Archives of Medical Science, 2010)
Introduction : The aim of the study was to explore the distribution of healthy people with different anti-tumour ability. Material and methods : Leukocytes were separated by the Ficoll-Hypaque density gradient centrifugal method. Then they were mixed with A549, MCF-7 and Hela cells at different ratios. The survival rate for target cells was observed and counted by Fluoroskan. Immune function for 200 healthy people was analysed by flow cytometry. Results : The results obtained by confocal microscopy revealed that human blood leukocytes possessed direct anti-tumour activity. The survival rate for tumour cells was the lowest in the condition of 20:1 ratio of effector cells to target cells. We speculated that in 200 healthy people the leukocyte capacity for killing MCF-7 cells is stronger than the leukocyte capacity for killing A549 cells and Hela cells. We also found that the distribution for 200 healthy people with different anti-tumour ability was different for different tumour cells. The number of healthy people with the strongest anti-tumour ability was highest when the target cells were MCF-7 cells. Moreover, the survival of A549, MCF-7 and Hela cells was correlated with T, B and NK lymphocytes. Conclusions : From the above, we can select healthy individuals with strong anti-tumour ability as anti-tumour donors according to their distribution with different anti-tumour ability, which opened up a new direction for fighting human cancer.